Analisis Jaminan Perorangan (Personal Guarantor) Dalam Perkara Kepailitan Ditinjau Dari Perspektif Hukum Dan Hak Asasi Manusia - Serlika Aprita; Devi Sri Astuti; Siti Sarah; Lulu Larasari; Diah Pitaloka Harin (JUSTICIA SAINS - Jurnal Ilmu Hukum, 2023)
Bankruptcy personal guarantee that is bankrupt without first bankrupting the main debtor in the Supreme Court Decision Number 141/PK/Pdt.Sus/Pailit/2016 whether it is in accordance with the provisions of the applicable legislation and to find out the application and consideration of the judge in deciding the case in this case. This study aims to make everyone who wants to be a guarantor of the debtor understand the applicable rules regarding individual guarantees. This research method uses a normative juridical approach. Normative juridical is where the researcher refers to the legal norms that exist in laws and regulations, literature, expert opinions, and papers. The results of this study indicate that the Judge in Decision Number 141/PK/Pdt.Sus/Pailit/2016 bankrupt the personal guarantee without first insolventing the main debtor because the personal guarantee has relinquished all its privileges, although according to the researcher there are still problems related to the list. BI Checking in showing the existence of other creditors.